Effective leadership styles and their impacts on employee productivity / Nur Solehah Izzat Ullah Sheikh and Dr Norizan Anwar - Izzat Ullah Sheikh, Nur Solehah; Anwar, Norizan (Faculty of Information Management, 2022)
Leaders are not limited to selected profession. Every profession, i.e., librarian, engineer, doctor who are devoted and talented employees can become successful leaders. Management strategies and employee motivation appear to be an important determinant towards the corporate success. Thus, this research sought to identify the leadership style of librarian and to examine how they affect the performance of employers in academic libraries. On top of that, this study also would like to examine how leadership philosophies affect worker productivity.